2022
DOI: 10.1021/acs.joc.1c02556
|View full text |Cite
|
Sign up to set email alerts
|

LiBr-Catalyzed C3-Disulfuration between Indole and N-Dithiophthalimide

Abstract: A simple, green halide-catalyzed protocol for disulfuration of indole derivatives with N-dithiophthalimides has been developed. This C–H disulfide reaction proceeded smoothly at room temperature with economical LiBr as catalyst, providing an effective method for the synthesis of novel unsymmetrical disulfides. A series of 3-dithioindole derivatives were obtained in high yields with good functional group tolerance; moreover, the wide scope of Harpp reagents (aryl, benzyl, primary, secondary, tertiary) confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Very recently, Pan and coworkers developed a simple and green LiBr‐catalyzed protocol for the C3‐disulfuration of indole derivatives 38 with N ‐dithiophthalimides ( 12 , Harpp reagents) under ambient conditions (Scheme 14). [110] The reaction does not require transition metal catalysts and strong bases but employs cost‐effective LiBr as the sole catalyst. The protocol exhibited a broad substrate scope, allowing the transformations across a vast range of N−H/N−Me/N−Bn indoles and aryl, benzyl, primary/secondary/tertiary alkyl Harpp reagents.…”
Section: C−h Disulfurationmentioning
confidence: 99%
“…Very recently, Pan and coworkers developed a simple and green LiBr‐catalyzed protocol for the C3‐disulfuration of indole derivatives 38 with N ‐dithiophthalimides ( 12 , Harpp reagents) under ambient conditions (Scheme 14). [110] The reaction does not require transition metal catalysts and strong bases but employs cost‐effective LiBr as the sole catalyst. The protocol exhibited a broad substrate scope, allowing the transformations across a vast range of N−H/N−Me/N−Bn indoles and aryl, benzyl, primary/secondary/tertiary alkyl Harpp reagents.…”
Section: C−h Disulfurationmentioning
confidence: 99%
“…However, most of the literature reported that the reaction was carried out using thiol as a substrate, with a bad smell and low commercial value . Thus, considerable efforts had been spent to develop alternative reagents as S-S sources to synthesize disulfides, for example, RSSSSR, RSSLG, NuSSNu, RSSAc, and RSSTs (Scheme b).…”
Section: Introductionmentioning
confidence: 99%
“…Since the synthesis of the Harpp reagents in 1971, it has found widespread application as an electrophilic reagent in the total synthesis of natural products . In recent years, researchers have explored new avenues for the use of the Harpp reagents . In 2019, the Wang group developed a copper-catalyzed coupling reaction between the Harpp reagent and phenylboronic acid.…”
mentioning
confidence: 99%